The effects of synchronous music on patients undergoing magnetic resonance imaging - Földes, Zsuzsa (2016)
Anxiety and claustrophobic reactions in Magnetic Resonance Imaging (MRI) lengthen the duration of examinations through increasing need of scan repetition, furthermore the need of anaesthesia makes the process costly. The sedative and alleviative effect of music is widely used in therapeutics, but in related research, music was only used with its original tempo as an intervention to reduce anxiety among MRI patients. 60 outpatients were examined in the Diagnostic Centre of Pécs to test whether the sedative effect of music can be improved by synchronizing it to the rhythm of the gradient pulsation, therefore reducing the effect of loud noises on the perception of music. The patients were assigned into three groups, namely a non-music (control), an original tempo (random) and a synchronized (synchron) group. MAX 7 was used for time stretching. There was a statistically significant interaction between the intervention and time (between pre- and post-intervention) on STAI-State anxiety level, F(2, 57) = 5.705, p = .006, partial η2 = .167. Results showed that the post-intervention state anxiety score significantly decreased in both music groups (random: M = 4.8, SE = 1.56, p = .006; synchron: M = 6.95, SE = 1.61, p < .001), while it did not change significantly in the control group. Median Visual Analogue Scale (VAS) scores examining the overall experience of the examination were statistically significantly different between groups, χ2(2) = 12.1, p = .002, η2 = 0.21, suggesting that music intervention made the examination more pleasant for the participants. Median pre-intervention state anxiety score was statistically significantly higher in females (Mdn = 36.00) than in males (Mdn = 30.00), U = 589.50, z = 2.142, p = .032, η2 = .08. The thematic analysis of the open-ended questions suggests that music and the headphones/earplugs work as a noise cancellation tools for the participants; furthermore, music caused a positive change in the environment and provided a help. Music distracts attention from the examination, relaxes patients and is seen as care and a desirable intervention in the future.